Enhanced photocatalytic activities of vandium and molybdenum co‐doped strontium titanate under visible light. Issue 4 (15th April 2019) - Hoang, Van‐Quoc‐Truong; Phan, T‐Que-Phuong; Senthilkumar, Velusamy; Doan, Van‐Thuan; Kim, Yong Soo; Le, Minh‐Vien
Abstract: In this report, undoped, mono and co‐doped perovskite strontium titanate (SrTi1−( x + y ) Mo x V y O3 ) were synthesized by the sol‐gel method, and their physical and optical properties were investigated. Furthermore, the photocatalytic degradation activities of the synthesized powders were conducted in 10 ppm methylene blue solution under visible‐light irradiation. A maximum degradation efficiency of 91.5% was achieved in SrTi0.9 Mo0.05 V0.05 O3 powder whereas only 59.9% of degradation was found in undoped SrTiO3 . The improved efficiency in co‐doped SrTiO3 was due to the doping of metal cations, Mo +6 and V +5 in the host lattice, which created impurity defect states thereby effectively reducing the bandgap energy of the semiconductor.